2020
DOI: 10.13052/ijfp1439-9776.2113
|View full text |Cite
|
Sign up to set email alerts
|

IJFP-2018-0015 - Robust Control Design for an Inlet Metering Velocity Control System of a Linear Hydraulic Actuator

Abstract: In this paper, we consider a hydraulic system in which the velocity is controlled using an inlet-metered pump. The flow of the inlet-metered pump is controlled using an inlet metering valve that is placed upstream from a fixed displacement check valve pump. Placing the valve upstream from the pump reduces the energy losses across the valve. The multiplicative uncertainty associated with uncertain parameters in an inlet metering velocity control system is studied. Six parameters are considered in the uncertaint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…( 14) and Eq. ( 15) respectively ( 14) (15) The next stage is to define the system's uncertainty ant its modeling.…”
Section: Stability Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…( 14) and Eq. ( 15) respectively ( 14) (15) The next stage is to define the system's uncertainty ant its modeling.…”
Section: Stability Analysismentioning
confidence: 99%
“…When the controller design is developed based on both performance and uncertainty, the structured matrix, , is considered [15]. This matrix is defined as shown in Eq.…”
Section: Figure 2: the Block Diagram Of The Feedback Control System With The Weightsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have been conducted on the hydrostatic transmissions and improving stability and performance of the hydrostatic transmission. Uncertainty of the inlet metering velocity control system was proposed in [4]. In that work, PID and H∞ were designed.…”
Section: Introductionmentioning
confidence: 99%
“…The system with the designed controller showed reasonable response under the parametric uncertainty conditions. PID and H-infinity controller were designed in [20] for a hydraulic actuator system. The results showed that the system with H-infinity controller performs better than the PID controller.…”
Section: Introductionmentioning
confidence: 99%